1983
DOI: 10.1079/bjn19830043
|View full text |Cite
|
Sign up to set email alerts
|

Storage of milk powders under adverse conditions

Abstract: 1. Whole-milk powders containing 25 g water/kg were stored for up to 9 weeks in sealed aluminium containers at elevated temperatures. Lysine and other essential amino acids were measured by chemical and microbiological methods.2. Storage at 60' resulted in the progressive formation of lactulosyl-lysine. After 9 weeks, 30% of the lysine groups were present in this form. The powders still retained their natural colour and the levels of tryptophan, methionine, cyst(e)ine and leucine remained unchanged.3. Storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Furosine content has been used to estimate the percentage of blocked lysine in samples similar to those used in this study, such as different types of milk subjected to varied thermal treatments (Bujard  Finot, 1978;Finot, Deutsch  Bujard, 1981;Evangelisti et al, 1999a) and during storage (Hurrell, Finot  Ford, 1983), and also in cereal and milk products (Erbersdobler  Hupe, 1991;Pizzoferrato et al, 1998;Evangelisti, Calcagno, Zunin  Nardi, 1999b). …”
Section: Lysine Blockage Through Storage Via the Furosine Methodsmentioning
confidence: 99%
“…Furosine content has been used to estimate the percentage of blocked lysine in samples similar to those used in this study, such as different types of milk subjected to varied thermal treatments (Bujard  Finot, 1978;Finot, Deutsch  Bujard, 1981;Evangelisti et al, 1999a) and during storage (Hurrell, Finot  Ford, 1983), and also in cereal and milk products (Erbersdobler  Hupe, 1991;Pizzoferrato et al, 1998;Evangelisti, Calcagno, Zunin  Nardi, 1999b). …”
Section: Lysine Blockage Through Storage Via the Furosine Methodsmentioning
confidence: 99%
“…Other study (Hurrell et al, 1983) has also reported that the lactulose concentration of the UHT milk was considerably higher than in nonfat dry milks. However, most of the UHT milk samples showed furosine concentration much lower than those of nonfat dry milk; this is because the extent of the Maillard reaction depends not only on the time and temperature of storage but also on the moisture content and the composition of the product.…”
Section: Introductionmentioning
confidence: 95%
“…Different chemical methods (guanidation, reduction with sodium borhydride, fluorodinitrobenzene direct method and indirect difference method, dye-binding lysine) have been compared [8,20,21], the conclusion being that the determination of furosine and the Carpenter method (1960) are the most appropriate for estimating reactive lysine in milk. However, direct application of the spectrophotometric Carpenter method (1960) to foods having high carbohydrate or reducing sugar contents is not possible, because interfering compounds can be formed with the subsequent overestimation of reactive lysine.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the thermal treatment applied in the manufacturing process and the effects of storage can be evaluated through the losses of available lysine (a specific marker of MR) [2,3]. Lactulosyl-lysine (e-N-deoxy-lactulosil-lysine), formed in the Amadori rearrangement of lactosyl amine, is the first intermediate compound of MR in milk, and is used as an indicator of the first step of the MR. Furosine detected for the first time in an acid hydrolysate of powdered milk [4] and identified, synthesized and characterized by Finot et al [5][6][7], results from the acid hydrolysis of the Amadori compound and permits the determination of lactulosyl-lysine [8][9][10]. Furosine content yields an estimation of blocked and therefore non-reactive lysine [8,[10][11][12], and is considered the most specific indicator of the first MR steps.…”
Section: Introductionmentioning
confidence: 99%